1996
DOI: 10.1159/000217273
|View full text |Cite
|
Sign up to set email alerts
|

Are Low-Molecular-Weight Heparins Useful for the Prophylaxis and Treatment of Arterial Thrombi?

Abstract: The pharmacologic specificity of low-molecular-weight heparins (LMWHs) has enabled multiple attractive developments in the prophylaxis and treatment of arterial thrombosis. Their high antithrombotic potency associated with a potentially lower induced bleeding risk, the lack of platelet interaction, the prevention of myointimal hyperplasia, and the lower incidence of heparin-induced thrombocytopenia, are major advantages. New studies in cardiology and vascular surgery demonstrate a high efficacy for LMWHs assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…On the basis that LMWH is effective in prevention of deep venous thrombosis after vascular surgery and after general surgery 4 and that LMWH is useful also to prevent arterial thrombi, both clinically 5 and experimentally, 6 we compared a single dose of LMWH during vascular surgery before vascular clamping with the same regimen using UFH. Further, the better bioavailability and longer plasma half-life of LMWH would be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis that LMWH is effective in prevention of deep venous thrombosis after vascular surgery and after general surgery 4 and that LMWH is useful also to prevent arterial thrombi, both clinically 5 and experimentally, 6 we compared a single dose of LMWH during vascular surgery before vascular clamping with the same regimen using UFH. Further, the better bioavailability and longer plasma half-life of LMWH would be of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…4 LMWHs have a number of pharmacodynamic and pharmacokinetic advantages over UH that would favor the use of LMWH instead of heparin for arterial indications. 7 For example, LMWHs are more resistant than heparin to neutralization by platelet factor 4, 8 which is released from activated platelets present at the site of arterial thrombus formation. In addition, reliable anticoagulation can be achieved with LMWHs by subcutaneous dosing without monitoring, 9 thereby providing convenient antithrombotic therapy that can be easily maintained for a prolonged time.…”
mentioning
confidence: 99%
“…11 However, recent evidence indicates that LMWHs are safe and effective antithrombotic agents for arterial thrombotic diseases. 7 For example, preclinical studies have demonstrated that LMWHs improve reflow after thrombolysis in canine models of thrombosis. 12,13 Clinically, a small trial provided evidence to support the potential use of enoxaparin instead of heparin as adjunctive therapy during thrombolysis with streptokinase.…”
mentioning
confidence: 99%
“…This has most frequently been accomplished with oral coumadin, but the hypercoagulable state in some patients is resistant to this agent. Recent reports indicate low molecular weight heparins are as effective as unfractionated heparin in preventing and treating thrombotic states, but there are few reports of their use in patients with Trousseau's syndrome or for arterial thrombosis [9,10]. Because of convenient dosing schedules and ease of administration) low molecular weight heparin may provide an attractive alternative long-term prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%